2007
DOI: 10.3123/jemsge.29.11
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Human Hepatoma Cell Line HepG2-A10 for a Reporter Gene Assay of Arylhydrocarbon Receptor Activators

Abstract: To establish a human hepatic cell line for a convenient reporter gene assay of arylhydrocarbon receptor (AhR) activators, the chimera plasmid containing xenobiotic responsible element (XRE), minimal SV40 promoter, and luciferase reporter gene and the expression vector pRC/CMV containing a neomycin-resistant gene were co-transfected into a human hepatoma cell line, HepG2. Then, antibiotic (G418)-resistant HepG2 cells were selected and cloned. A cell clone, HepG2-A10, showed the highest responsibility to 3-methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…17,18) Clone HPL-A3 showed the greatest ability to induce chemical-mediated luciferase activity among the clones examined. Therefore, HPL-A3 was used for further experiments.…”
Section: Construction Of Hpxr Expression Plasmidmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18) Clone HPL-A3 showed the greatest ability to induce chemical-mediated luciferase activity among the clones examined. Therefore, HPL-A3 was used for further experiments.…”
Section: Construction Of Hpxr Expression Plasmidmentioning
confidence: 99%
“…Gene Expression of CYP3A4 and Its Positive Transcriptional Regulators Constitutive gene expression levels of the positive transcriptional nuclear receptors (PXR, VDR, and CAR) of the CYP3A4 gene and of their partner protein, retinoid X receptor α (RXRα), were determined by reverse transcription (RT)-PCR method 17,18) with the appropriate primer sets. [19][20][21][22][23] The primer sets and amplification protocol used are shown in Table 1.…”
Section: Construction Of Hpxr Expression Plasmidmentioning
confidence: 99%
“…To determine a mechanism for the Nicmediated induction of the CYP1 mRNAs, the ability of Nic to activate AhR was examined using a HepG2-A10 cell line, which was established from HepG2 cells for screening of AhR activators including AhR ligands. (19) The results indicated that Nic weakly activated AhR (inducing luciferase), suggesting that Nic-mediated induction likely occurs only partially through activation of AhR.…”
Section: Discussionmentioning
confidence: 96%
“…A human hepatoma cell line, HepG2, was obtained from the ATCC (Manassas, VA, USA), and HepG2‐A10 cells were previously established from HepG2 cells for use in a convenient reporter gene assay of AhR activators in our laboratory. ( 19 ) The HepG2 and HepG2‐A10 cells were maintained in DMEM supplemented with 5% FBS, 4 mM l ‐glutamine and 60 μg/mL kanamycin sulfate at 37°C in a 5% CO 2 humidified incubator.…”
mentioning
confidence: 99%